Bridging the Gap: The Reality of Digital Technology Integration by Indonesian Pre-service EFL Teachers - Limbong, Effendi; Setiawan, Iwan; Hamilton, Amy (Script Journal: Journal of Linguistics and English Teaching, 2024)
Background: This research investigates the integration of digital technology into teaching practices among pre-service English as a Foreign Language (EFL) teachers in Indonesia, using the Technological Pedagogical Content Knowledge (TPACK) framework. The exploration focuses on the contextual challenges and limited technological infrastructure that hinder effective technology use during teaching practicums. Methodology: Employing a qualitative case study design, the research involved six pre-service teachers from three junior high schools in Indonesia. Data were collected through Video-Stimulated Recall (VSR) interviews, direct observations, and analysis of teaching materials, including lesson plans and multimedia resources used in classroom settings. Findings: The findings reveal that while pre-service teachers were theoretically prepared for integrating technology into education, practical implementation was often compromised by infrastructural deficiencies. Teachers frequently encountered issues such as insufficient internet access and lack of support from supervisory staff, which forced them to rely on basic and offline technological tools despite their preparedness to employ more sophisticated resources. Conclusion: The research underscores a significant gap between the theoretical training provided by teacher education programs and the practical realities in Indonesian schools. It suggests that enhancing technological infrastructure and mentorship in these settings is crucial to effectively translate pedagogical and content knowledge into technology-integrated teaching practices. Originality: This research contributes to the field by highlighting the specific challenges faced by pre-service teachers in developing countries like Indonesia and provides empirical evidence on the discrepancies between their training and actual teaching experiences. The study advocates for an integrated approach in teacher education that aligns theoretical knowledge with practical abilities to navigate technological constraints